THE APPLICATION OF PARTNER READING STRATEGY IN IMPROVING READING COMPREHENSION - Reka Maulidina; Ferry Rita (Tadulako University, 2021)
The objective of this research is to find out that the Application of Partner Reading Strategy improves students’ reading comprehension. The population was the grade Eight students at SMP Negeri 1 Toribulu. The researcher used quasi- experimental design. The researcher sample were VIII A as the experimental group which consisted of 28 students and VIII B as the control group which consisted 28 student. The test was administered twice: pre test and post test. The data were analyzed statically in order to find out the significant achievement of the students in the pre test and the post test. The experimental group was given the treatment by applying Partner Reading Strategy, while the control group was taught reading descriptive text with conventional strategy. The instrument used in collecting data was a test given as pre-test and post-test. The result of tests shows that the mean score of experimental group was 88.0 from 52,3 in the pretest, and the control group was 75 from 54,5 in the pretest. This score shows that the mean score of the experimental group is higher than the mean score of the control group on posttest. By applying one-tailed test at 0.05 level of significance with 54 degree of freedom (df), it is found that, the tcounted value of (1,87) is greater than ttable value (1.67). It confirms that, the research hypothesis was accepted. Based on the result, it concludes that, Partner Reading Strategy improves students’ reading comprehension at the eight grade students of SMP Negeri 1 Toribulu.